2016
DOI: 10.1111/apt.13629
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of severe recurrent hepatitis C after liver transplantation in HIV infected patients using sofosbuvir‐based therapy

Abstract: Sofosbuvir-based regimens are safe, well-tolerated and provide high rates of SVR in HCV-HIV co-infected patients with severe recurrence after-liver transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
2
9
1
Order By: Relevance
“…Data of 13 patients treated pre-OLT have been published: SVR was observed in 9 of 10 patients treated with optimal therapy (90%) and in 1 of 3 (33.3%) patients treated with SOF and RBV. Six small series reported the data of 48 patients treated post-OLT: the SVR12 rate was 90%, but it topped at 100% when evaluating only the 28 patients treated with optimal regimens [5–10]. These and our results confirm the data observed in HCV-monoinfected individuals in the same settings [4].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Data of 13 patients treated pre-OLT have been published: SVR was observed in 9 of 10 patients treated with optimal therapy (90%) and in 1 of 3 (33.3%) patients treated with SOF and RBV. Six small series reported the data of 48 patients treated post-OLT: the SVR12 rate was 90%, but it topped at 100% when evaluating only the 28 patients treated with optimal regimens [5–10]. These and our results confirm the data observed in HCV-monoinfected individuals in the same settings [4].…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, sofosbuvir (SOF)-based therapies have showed high efficacy and tolerability in both OLT candidates and recipients [4]. So far, small series data in HIV/HCV-coinfected persons have been published, cumulatively reporting treatment in 13 OLT candidates and 48 recipients [5–10]. The aim of this study was to assess the impact of SOF-based anti-HCV, all oral treatment on OLT in PLWHIV.…”
mentioning
confidence: 99%
“…In this issue of Liver Transplantation , Araiz et al report an intent‐to‐treat survival analysis (ITTA) of HCV/HIV‐coinfected candidates listed for liver transplantation. This valuable analysis confirms previous US, Spanish, and French series reporting inferior outcomes following liver transplantation in the HCV/HIV coinfected liver recipient compared to mono‐infected HIV‐positive recipients. Most notably, this ITTA confirms that HCV/HCV coinfection is associated with a higher mortality on the waiting list than is observed in HCV mono‐infected candidates.…”
supporting
confidence: 86%
“…It is important to note that the ITTA was done in an era predating the introduction of the new direct‐acting agents effective in curing HCV. Treatment with these newer agents will undoubtedly improve survival in the HCV/HIV‐coinfected patients on the waiting list and following transplantation . With effective HCV clearance, it is possible that the MELD score will be a more accurate predictor of survival on the waiting list for the HCV/HIV‐coinfected recipient.…”
mentioning
confidence: 99%
“…Nevertheless, data on the efficacy and safety of DAAs in HCV/HIV‐coinfected LT recipients are limited to case series and individual case reports. The largest series was published by Campos‐Varela et al, who evaluated the outcome of a sofosbuvir (SOF)‐based compassionate use program in HCV/HIV‐coinfected LT recipients. The authors found that 20 patients with early recurrence of severe HCV infection or cirrhosis received SOF‐based antiviral therapy.…”
Section: Introductionmentioning
confidence: 99%